Witkacy i inni — ile może pomieścić jeden Staś? Witkacy i inni. Z kolekcji Stefana Okołowicza i Ewy Franczak, pod. red. B. Czubak i S. Okołowicza, Fundacja Profile, Warszawa 2011, 372 ss. - Cytacka, Agnieszka (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The question “how much there is to Witkacy” accompanies reading the album from “Witkacy and others” exhibition in Wilanów, that — as Piotr Sarzyński writes in his review — “covers everything that linked Witkacy with photography”. The exhibition and the catalogue are a large project which would not be possible if not for Stefan Okołowicz and Ewa Franczak, owners of hundreds of photographs by Stanisław Ignacy Witkiewicz. Their contribution to making Witkacy-the photographer a figure in art history cannot be overestimated, and neither can their efforts of many years to keep his photographic self-portraits in public awareness. It was Okołowicz who showed the world Witkacy photographing. For thirty years, he has been collecting his works: paintings, drawings, photographs. He published the album “Against nothingness” and significantly contributed to the emergence of psychoholism. In his recent project, he marked out his presence and his role in propagation of Witkiewicz’s art more clearly than the previous time. He seemingly placed himself aside. In fact, he put himself in the center of the whole project. He showed, as Wojciech Nowicki put it in one of “Fundus’” essays, that photography cannot exist without an archivist.